The Relationship of the Administrative Process of the Lahat Regency Industry and Trade Service to Home Industry Licensing: Hubungan Proses Administrasi Dinas Perindustrian Dan Perdagangan Kabupaten Lahat Terhadap Perizinan Industri Rumahan - Anggraini, Mei Reza; Ghofur, Nilman (JURNAL ISIP VOICE : Jurnal Ilmu Sosial dan Ilmu Politik, 2024)
The Industry and Trade Office of Lahat Regency is one of the institutions used by the community to provide licensing services, especially business permits. As an UMKM (Micro, Small, and Medium Enterprises) that is just starting a business with Home Industry, the role of the Trade Office is very much needed. This scientific paper shows the purpose that there is an administrative process carried out by the Trade Office of Lahat Regency regarding licensing of UMKMs, especially Home Industry. The descriptive qualitative method is the most appropriate in this study by conducting a literature study and also short interviews from primary and secondary data sources to strengthen this research. This study explains how the author implements business capital and business licensing needs and the UMKM Culinary Business Plan which discusses that the Trade Office plays a very important role in the progress of Home Industry. The results of the study indicate that the capability of the administrative process in licensing UMKMs by the Trade Office is true, but it turns out that the Trade Office is not the main actor in granting permits, the Trade Office only acts as an intermediary through the OSS (Online Single Submission) application.